lim ((x+h)^-2 - x^-2)/h as h->0 - Wolfram|Alpha

I don't know where the answer is coming from. What are the missing steps?

Printable View

- Sep 17th 2011, 09:02 AMStuck Mandifferentiating a function from first principles
lim ((x+h)^-2 - x^-2)/h as h->0 - Wolfram|Alpha

I don't know where the answer is coming from. What are the missing steps? - Sep 17th 2011, 09:06 AMStuck ManRe: differentiating a function from first principles
I have found I have done this question before. It involves making a common denominator.

- Sep 17th 2011, 09:06 AMProve ItRe: differentiating a function from first principles
- Sep 17th 2011, 11:17 AMskeeterRe: differentiating a function from first principles
$\displaystyle \lim_{h \to 0} \frac{\frac{1}{(x+h)^2} - \frac{1}{x^2}}{h}$

$\displaystyle \lim_{h \to 0} \frac{\frac{1}{(x+h)^2} - \frac{1}{x^2}}{h} \cdot \frac{x^2(x+h)^2}{x^2(x+h)^2}$

$\displaystyle \lim_{h \to 0} \frac{x^2 - (x+h)^2}{h \cdot x^2(x+h)^2}$

finish it ...